The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1097/00006534-199609001-00018
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Ischemia-Reperfusion Injury with a Synthetic Metalloprotein Superoxide Dismutase Mimic, SC52608

Abstract: Superoxide dismutase (SOD) scavenges free superoxide radicals generated during reperfusion of ischemic tissue and decreases cellular injury. A synthetic manganese-based metalloprotein superoxide dismutase mimic, SC52608 (Monsanto Co.), was tested in the isolated rabbit rectus femoris muscle flap to determine its effects on ischemia-reperfusion injury. The results of our experiments analyzing 38 isolated rectus femoris muscles in 19 New Zealand White rabbits show that administration of SC52608 at the onset of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
3
4
0
Order By: Relevance
“…In our model, the swelling present after 24 h of reperfusion increased the upper-thigh cross-sectional area by 30%. This figure is similar to those from a rabbit experimental model 56 , in which there was a 38% in the crosssectional area after 4 h of ischemia and 24 h of reperfusion. Regarding the weight of the gastrocnemius muscle, we observed a 10% increase, while Bonheur 18 reported a 22% increase, after 3 h of ischemia and 24 h of reperfusion.…”
Section: Discussionsupporting
confidence: 87%
“…In our model, the swelling present after 24 h of reperfusion increased the upper-thigh cross-sectional area by 30%. This figure is similar to those from a rabbit experimental model 56 , in which there was a 38% in the crosssectional area after 4 h of ischemia and 24 h of reperfusion. Regarding the weight of the gastrocnemius muscle, we observed a 10% increase, while Bonheur 18 reported a 22% increase, after 3 h of ischemia and 24 h of reperfusion.…”
Section: Discussionsupporting
confidence: 87%
“…The pathological findings, after 3 h of ischemia and 24 h of reperfusion, showed that 80.7 ± 16.4% of the fibers were damaged. These figures correlate with those reported by McCormack et al [ 67 ], with 60% of the fibers damaged after 2 h of ischemia, and by Deune et al, with 80% of the fibers damaged after 4 h of ischemia [ 68 ]. FA pre-treatment reduced the number of damaged muscle fibers in each field by 20% (64 ± 17.1 vs. 80.7 ± 16.4; p < 0.001), resulting in a reduction in damage similar to that achieved in younger rats with the same treatment (52.1 ± 20.6% vs. 65.5 ± 14.1%; p < 0.001) [ 52 ].…”
Section: Discussionsupporting
confidence: 91%
“…Free radical scavengers including allopurinol, superoxide dismutase, catalase, and dimethyl sulfoxide, etc. have been examined and shown to attenuate I/R injury in various preparations [30]. However, there are also negative reports [31,32].…”
Section: Therapeutic Interventions Targeting I/r Injury Free Radical mentioning
confidence: 99%